2005
DOI: 10.1086/499623
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Dense Gas Tracers of Star Formation in our Galaxy to High- z Star Formation

Abstract: Observations have revealed prodigious amounts of star formation in starburst galaxies as traced by dust and molecular emission, even at large redshifts. Recent work shows that for both nearby spiral galaxies and distant starbursts, the global star formation rate, as indicated by the infrared luminosity, has a tight and almost linear correlation with the amount of dense gas as traced by the luminosity of HCN. Our surveys of Galactic dense cores in HCN 1−0 emission show that this correlation continues to a much … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

81
466
4
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(554 citation statements)
references
References 29 publications
81
466
4
3
Order By: Relevance
“…If SFR(radio) gives an accurate measure of SFR, then the results would mean that SFR(L T IR ) is a good tracer above 10 4.5 L ⊙ . This result would be consistent with the suggestion by Wu et al (2005b) that the L T IR traces star formation above that luminosity. Resolving YSOs in regions forming high mass stars is a next important step in further understanding of the use of these tracers.…”
Section: Combining Both Samplessupporting
confidence: 93%
“…If SFR(radio) gives an accurate measure of SFR, then the results would mean that SFR(L T IR ) is a good tracer above 10 4.5 L ⊙ . This result would be consistent with the suggestion by Wu et al (2005b) that the L T IR traces star formation above that luminosity. Resolving YSOs in regions forming high mass stars is a next important step in further understanding of the use of these tracers.…”
Section: Combining Both Samplessupporting
confidence: 93%
“…This interpretation was expanded upon by Wu et al (2005) and Wu et al (2010), who extended this study to dense clumps 20 within the Galaxy and found a similarly linear relation between L IR and HCN luminosity. Complementary work utilizing HCO + (J=3-2), which has a similar effective density as HCN (J=1-0) (Juneau et al, 2009), as well as high-visual extinction molecular gas as dense gas tracers have found roughly linear dense gas star formation laws for clumps within the Milky Way (Lada et al, 2010;Schenck et al, 2011).…”
Section: Physics Learned From the Milky Way And Local Galaxiesmentioning
confidence: 56%
“…Finally, our findings have also relevance for the extragalactic community, who make use of the HCN molecule to estimate the amount of dense molecular gas and correlate it to the star formation rate in galaxies (see Wu et al 2005, for a Galactic and extragalactic analysis on the matter). It is interesting that our mean value for the HCO + (1-0) to HCN(1-0) ratio of 0.74 for the IR-loud sub-sample is not greatly different than that (a median of 0.86) found by Krips et al (2008) for a sample of AGN and starburst galaxies (though with a variation from 0.48 to 1.5).…”
Section: Hco + (1-0) Versus Hcn(1-0)mentioning
confidence: 71%
“…HCN and HCO + are commonly used as tracers of the dense gas from which "bursts" of star formation emanate both in the Galactic and extragalactic contexts (Wu et al 2005;Gao & Solomon 2004). They have the advantage relative to CO that their dipole moments are high and hence that even their 3 mm transitions trace gas of density above ∼10 4 cm −3 .…”
Section: Hco + (1-0) Versus Hcn(1-0)mentioning
confidence: 99%